2019
DOI: 10.1093/gerona/glz216
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Acute Pain Treatment by Cognitive Status in Older Adults With Hip Fracture

Abstract: Background We examined the disparities in emergency department (ED) pain treatment based on cognitive status in older adults with an acute hip fracture. Methods Observational study in an academic ED in the Bronx, New York. One hundred forty-four adults aged 65 years and older with acute hip fracture were administered the Telephone Interview for Cognitive Status (TICS) while in the ED. The primary outcome was receipt of any pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…The World Health Organization defines palliative care as a practice that aims to improve the quality of life of persons with chronic illnesses by prioritizing prevention, early identification, assessment and treatment of pain along with associated psychological, spiritual and physical concerns. 5 Considering pain experienced by older adults is often undertreated by primary care physicians, [6][7][8] palliative care teams with physicians and other health care professionals trained specifically in pain management can ensure that older adults receive comprehensive and interdisciplinary support in coping with pain and difficult symptoms from their illnesses. While the field of palliative care has been growing steadily over time, 9 the urban-centric nature of palliative care programs and transportation issues pose significant challenges in accessibility, particularly for rural older adults who live in remote areas with little to no access to specialized services.…”
mentioning
confidence: 99%
“…The World Health Organization defines palliative care as a practice that aims to improve the quality of life of persons with chronic illnesses by prioritizing prevention, early identification, assessment and treatment of pain along with associated psychological, spiritual and physical concerns. 5 Considering pain experienced by older adults is often undertreated by primary care physicians, [6][7][8] palliative care teams with physicians and other health care professionals trained specifically in pain management can ensure that older adults receive comprehensive and interdisciplinary support in coping with pain and difficult symptoms from their illnesses. While the field of palliative care has been growing steadily over time, 9 the urban-centric nature of palliative care programs and transportation issues pose significant challenges in accessibility, particularly for rural older adults who live in remote areas with little to no access to specialized services.…”
mentioning
confidence: 99%
“…This review demonstrates that studies of components of ED care and emergency care needs for PLWDs are wide ranging with little depth on any topic. Studies on components of ED care for PLWDs included a comprehensive geriatric assessment and dedicated ED unit, 26 care partners in the ED and hospital care companions for PLWDs, 22,30 identifying delirium, 4,34,36 fall prevention, 41 admission to a home hospital program, 42 pain assessment and management, 21,28,31,32,43,44 palliative care, 23,37 and changes to the physical environment. 27,33 Four studies showed improvement in patient-centered outcomes or health services use: a comprehensive geriatric assessment and dedicated ED unit, 26 stimulation reduction and noncontact monitoring, 33 dementia companions, 22 and hospital at home program.…”
Section: Discussionmentioning
confidence: 99%
“…32 In another study of patients with hip fractures, patients with cognitive impairment were less likely to receive parenteral analgesia and received lower doses of analgesia than persons without cognitive impairment. 28 However, a different conference abstract demonstrated no difference in follow-up pain assessment or use of opioid analgesia. 21 Three studies described the development, validation, and use of the Pain Assessment IN Advanced Dementia (PAINAD) scale.…”
Section: Components Of Ed Carementioning
confidence: 97%
See 1 more Smart Citation
“…The role of the caregiver becomes even more critical when the patients' ability or capacity for decision-making is significantly compromised by cognitive impairment and the caregiver has to step in as a surrogate decision-maker. Prior studies found that, when compared with cognitively intact older adults, cognitively impaired ones are less likely to be treated for pain as serious as that of their counterparts (McDermott et al, 2014;Chang et al, 2019). Therefore, special attention needs to be paid to cognitively impaired older adults' needs for managing pain and symptoms from their chronic or serious illnesses.…”
Section: Palliative Care and Caregivers Of Cognitively Impaired Older Adultsmentioning
confidence: 99%